Athenry Dominican Friary, south nave wall, statue corbel - O'Donovan, Danielle (My University, 2008)
Statue corbel at south side of nave, moulding from top down comprises: abacus, quadrant, flat surface, quadrant, fillet, hollow chamfer, fillet, bell, scroll, fillet, flat surface, quadrant, quarter roll (upside-down scroll), fillet, bell, necking roll.
Keywords: scroll; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Gothic capitals (Architecture); Late Medieval; corbels; roll moldings